Natural history of a bighorn sheep pneumonia epizootic: Source of infection, course of disease, and pathogen clearance - Besser, Thomas E.; Cassirer, E. Frances; Lisk, Amy; Nelson, Danielle; Manlove, Kezia R.; Cross, Paul C.; Hogg, John T. (Ecology and evolution, 2021)
A respiratory disease epizootic at the National Bison Range (NBR) in Montana in 2016–2017 caused an 85% decline in the bighorn sheep population, documented by observations of its unmarked but individually identifiable members, the subjects of an ongoing long‐term study. The index case was likely one of a small group of young bighorn sheep on a short‐term exploratory foray in early summer of 2016. Disease subsequently spread through the population, with peak mortality in September and October and continuing signs of respiratory disease and sporadic mortality of all age classes through early July 2017. Body condition scores and clinical signs suggested that the disease affected ewe groups before rams, although by the end of the epizootic, ram mortality (90% of 71) exceeded ewe mortality (79% of 84). Microbiological sampling 10 years to 3 months prior to the epizootic had documented no evidence of infection or exposure to Mycoplasma ovipneumoniae at NBR, but during the epizootic, a single genetic strain of M. ovipneumoniae was detected in affected animals. Retrospective screening of domestic sheep flocks near the NBR identified the same genetic strain in one flock, presumptively the source of the epizootic infection. Evidence of fatal lamb pneumonia was observed during the first two lambing seasons following the epizootic but was absent during the third season following the death of the last identified M. ovipneumoniae carrier ewe. Monitoring of life‐history traits prior to the epizootic provided no evidence that environmentally and/or demographically induced nutritional or other stress contributed to the epizootic. Furthermore, the epizootic occurred despite proactive management actions undertaken to reduce risk of disease and increase resilience in this population. This closely observed bighorn sheep epizootic uniquely illustrates the natural history of the disease including the (presumptive) source of spillover, course, severity, and eventual pathogen clearance. This case report provides unprecedentedly detailed animal observations before, during, and after a severe bighorn sheep pneumonia outbreak and includes molecular detection of the causative primary pathogen, Mycoplasma ovipneumoniae, in its putative source, a nearby domestic sheep operation. As a result, this case report serves to advance our understanding of critical aspects of this important disease.